2017
DOI: 10.12691/jfnr-5-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of Cookie Made With Beeswax-Coconut Oil Organogels as Replacement for Shortening

Abstract: The effects of beeswax-coconut oil organogels (7.5%, 10.0%, 12.5%, 15.0% and 17.5% beeswax, wt) quality-related characteristics of shortening replaced cookies were evaluated. The following quality attributes were measured: organogels melting points, fatty acids contents, proximate composition, color, texture, spread factor, sensory evaluation, antioxidant activity and storage stability. Peroxide values of cookie extracts made with organogels were dramatically lower than that of cookie made with shortening (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…In 20% PDCF + AM rusk sample, the major fatty acid was lauric acid (44.8%) followed by myristic acid (19.0%). Similar fatty acid profiles were reported in the cookies prepared by replacing fat using coconut oil‐beeswax organogels (Sung & Lin, ). Lauric acid lowers the ratio of total to HDL cholesterol more than the other saturated fatty acids (Mensink et al ., ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In 20% PDCF + AM rusk sample, the major fatty acid was lauric acid (44.8%) followed by myristic acid (19.0%). Similar fatty acid profiles were reported in the cookies prepared by replacing fat using coconut oil‐beeswax organogels (Sung & Lin, ). Lauric acid lowers the ratio of total to HDL cholesterol more than the other saturated fatty acids (Mensink et al ., ).…”
Section: Resultssupporting
confidence: 80%
“…Dhankhar () reported that gluten‐free cookies could be prepared by substituting wheat flour with coconut flour to cater to the needs of celiac patients. According to Sung & Lin (), use of virgin coconut oil instead of shortening produced cookies with more greasy and less crispy characteristics but the quality was improved by incorporating beeswax. In the present study, work was undertaken to develop rusk without any added fat by replacing wheat flour with PDCF at different levels of 10%, 20% and 30% in a generally used rusk formulation.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in fat might be due to the nature of astaxanthin that is composed of 5% of free fatty acid, 70% of monoesters and 25% diesters. 39 Other compositions including ash, protein and carbohydrate showed no significant difference, meaning that the presence of astaxanthin in the cookies did not cause any changes in the component. Values are mean ± SD within a column with a different letter (a-c) are significantly different (p≤0.05).…”
Section: Physiochemical Evaluationmentioning
confidence: 89%
“…At a constant level of rice bran wax, increasing rice bran oil significantly decreased (p ≤ 0.05) the emulsion hardness, while at a constant level of rice bran oil, increasing rice bran wax significantly increased the emulsion hardness (p ≤ 0.05). Sung and Lin (2017) found that increasing the ratio of beeswax significantly increased the hardness and adhesiveness of organogel (p ≤ 0.05). This could be due to the straight-chain acids with up to 36 carbon skeletons which resulted in a strong network of gels forming during crystallisation.…”
Section: Rice Bran Shortening (Emulsion) Texturementioning
confidence: 96%